Developing a sustainability benchmarking system : a case study of the provincial government Western Cape’s immovable asset assessment pilot project - Meiring, Casper Johannes Knoetze (Stellenbosch : Stellenbosch University, 2014)
Thesis (MPhil)--Stellenbosch University, 2014.